THE IMPACT OF WATER DEFICIT AND INDUSTRIAL TREATMENT OF SEEDS ON GERMINATION, DEVELOPMENT, VIGOR AND DRY MATTER PRODUCTION IN SOYBEAN SEEDLINGS - Pinheiro, S. B.; Costa, H. J. S.; Freitas, J. M.; Frade, P. R.; Silva, A. A.; Pereira, C. S. (Revista Brasileira de Engenharia de Biossistemas, 2019)
Soybean cultivation requires a high level of quality in relation to the seeds employed, besides being very dependent on the water condition. Within this systematic, this study evaluated the impact of water deficit on seed germination in soybean crop. Twelve treatments were evaluated, with 4 replications in each, totaling 50 soybean seeds per repetition, comparing the yield of the seeds treated industrially with standak top 200 ml every 100 kg of seeds (Piraclostrobina 25g/L + thiofanate Methyl 225g/L + fipronil 713g/L), with fungicides compared to untreated seeds. The results showed that the absence of water up to 14 days did not impact on productivity and productive yield. However, after this period, the absence of moisture influenced the physiological quality of the seeds, compromising the final stand. The analyses made about the influence of temperature and humidity were not significants. Another conclusion of this experiment was that the treated seeds obtained a result below that obtained by untreated seeds. From the analyses performed, it is assumed that the treatment used in the industrially treated seeds has not been adequately performed, causing phytotoxicity in the seed or injuries caused at the time of the insertion of the mixture that compromised the Physiological and chemical quality of the treated seed and, for this reason, its yield did not overcome the obtained by untreated seeds.